Comparative analysis of arteriolar Doppler ultrasound parameters in hypertensive patients with or without Type 2 diabetes mellitus - V. S. Volkov; E. V. Rudenko; O. B. Poselyugina (Кардиоваскулярная терапия и профилактика)
Aim. Using the Doppler ultrasound method, to describe functional status of arterioles in patients with essential arterial hypertension (AH) and individuals with Type 2 diabetes mellitus (DM-2) and concomitant AH. Material and methods. The study included 90 AH patients and 83 patients with DM-2 and AH. Systolic (Vs, cm/s), diastolic (Vd, cm/s), and mean (Vm, cm/s) arteriolar blood flow velocity was measured using the Miniplex Doppler device. The subsequent spontaneous changes in blood flow velocity were registered for one minute and presented as percentages. Results. The maximal blood flow velocity was observed in AH patients, followed by healthy controls and patients with DM-2 and AH. The Vs variation was the largest in healthy people, smaller in AH patients, and the smallest in participants with AH and DM-2. The maximal Vd variation was observed in AH patients, followed by patients with AH and DM-2 and healthy controls. Conclusion. The assessment of arteriolar blood flow velocity provides information about arteriolar tonus and its dynamics over time.